Oxygen gradient induced in microfluidic chips can be used as a model for liver zonation - Ghafoory, Shahrouz; Stengl, Christina; Kopany, Stefan; Mayadag, Mert; Mechtel, Nils; Murphy, Brennah; Schattschneider, Sebastian; Wilhelmi, Niklas; Wölfl, Stefan (Cells, 2022)
Availability of oxygen plays an important role in tissue organization and cell-type specific metabolism. It is, however, difficult to analyze hypoxia-related adaptations in vitro because of inherent limitations of experimental model systems. In this study, we establish a microfluidic tissue culture protocol to generate hypoxic gradients in vitro, mimicking the conditions found in the liver acinus. To accomplish this, four microfluidic chips, each containing two chambers, were serially connected to obtain eight interconnected chambers. HepG2 hepatocytes were uniformly seeded in each chamber and cultivated under a constant media flow of 50 µL/h for 72 h. HepG2 oxygen consumption under flowing media conditions established a normoxia to hypoxia gradient within the chambers, which was confirmed by oxygen sensors located at the inlet and outlet of the connected microfluidic chips. Expression of Hif1α mRNA and protein was used to indicate hypoxic conditions in the cells and albumin mRNA and protein expression served as a marker for liver acinus-like zonation. Oxygen measurements performed over 72 h showed a change from 17.5% to 15.9% of atmospheric oxygen, which corresponded with a 9.2% oxygen reduction in the medium between chamber1 (inlet) and 8 (outlet) in the connected microfluidic chips after 72 h. Analysis of Hif1α expression and nuclear translocation in HepG2 cells additionally confirmed the hypoxic gradient from chamber1 to chamber8. Moreover, albumin mRNA and protein levels were significantly reduced from chamber1 to chamber8, indicating liver acinus zonation along the oxygen gradient. Taken together, microfluidic cultivation in interconnected chambers provides a new model for analyzing cells in a normoxic to hypoxic gradient in vitro. By using a well-characterized cancer cell line as a homogenous hepatocyte population, we also demonstrate that an approximate 10% reduction in oxygen triggers translocation of Hif1α to the nucleus and reduces albumin production.